2023
DOI: 10.1094/pdis-06-22-1512-re
|View full text |Cite
|
Sign up to set email alerts
|

Differential Seasonal Prevalence of Yellowing Viruses Infecting Melon Crops in Southern California and Arizona Determined by Multiplex RT-PCR and RT-qPCR

Abstract: Viruses transmitted by the whitefly (Bemisia tabaci) are an increasing threat to cucurbit production in the southwestern United States as well as many other cucurbit production regions throughout the world. The crinivirus, cucurbit yellow stunting disorder virus (CYSDV), has severely impacted melon production in California and Arizona since its introduction to the region in 2006. Within the past few years, another crinivirus, cucurbit chlorotic yellows virus (CCYV), and the whitefly-transmitted ipomovirus, squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…In this study, a putative novel crinivirus was identified and molecularly characterized. The closest relative of CuCV appears to be CYSDV, a Bemisia-tabaci -transmitted crinivirus causing extensive infections of cucurbit crops in many warm and temperate production areas [ 29 , 30 , 31 , 32 , 33 ]. The taxonomy of CuCV was first determined based on the low complete genome identity (65–69%) with CYSDV isolates compared to the 99% intraspecific similarity of CYSDV isolates ( Tables S7 and S8 ), despite the extensive and discontinuous geographical distribution and different years of collection.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a putative novel crinivirus was identified and molecularly characterized. The closest relative of CuCV appears to be CYSDV, a Bemisia-tabaci -transmitted crinivirus causing extensive infections of cucurbit crops in many warm and temperate production areas [ 29 , 30 , 31 , 32 , 33 ]. The taxonomy of CuCV was first determined based on the low complete genome identity (65–69%) with CYSDV isolates compared to the 99% intraspecific similarity of CYSDV isolates ( Tables S7 and S8 ), despite the extensive and discontinuous geographical distribution and different years of collection.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011 the crinivirus cucurbit chlorotic yellows virus (CCYV) was first reported in Europe, specifically in Greece, causing symptoms similar to those produced by CYSDV (Orfanidou et al., 2014). Even though CCYV has spread to other Mediterranean countries (Maachi et al., 2022), it has not yet been as problematic in open field conditions as it is in the United States, where both CCYV and CYSDV have been detected in a high percentage of samples tested on both the East and West Coasts (Kavalappara et al., 2021; Mondal et al., 2023). Another whitefly‐transmitted virus that causes severe economic losses in greenhouse and open‐field cucurbit crops is the tomato leaf curl New Delhi virus (ToLCNDV), that was first reported in Europe in 2012 in Spain (Juárez et al., 2014) and is rapidly spreading.…”
Section: Introductionmentioning
confidence: 99%